Direction of Trade Statistics Yearbook, 2008. (Direction of Trade Statistics; Direction of Trade Statistics ;, 2009)
The Direction of Trade Statistics yearbook gives seven years of data for about 184 countries and two sets of world and area summaries: world and area trade as seen by the reporting countries and as seen by the partner countries to those transactions. The yearbook is usually published in September.